PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY TERHADAP HASIL BELAJAR SISWA - Andriono Manalu (JURNAL ILMIAH MAKSITEK, 2018)
This study aims to determine the effect of the Guided Inquiry learning model on student learning outcomes in the subject matter Substance and its form in Class VII of the First Semester of State Middle School 2 Siantar T.A 2017/2018. This type of research is pre-experimental design. The population in the study were all VII grade students consisting of 6 classes with samples of class VII1 as a trial class of 32 people taken by random sampling using a guided inquiry learning model. The instrument used to determine student learning outcomes is a test of learning outcomes in the form of multiple choices with a number of 20 questions consisting of 4 answer choices, and all the questions given must be valid categories. Before being given treatment, the pilot class was given a pretest to find out the initial abilities of students who obtained an average pretest score of 43.28. After being given the treatment of the guided inquiry learning model, the posttest mean score was 73.13. After obtaining the average student N-Gain score is 0.52 with the medium category. The observation results of learning with guided inquiry learning models have been carried out at each stage of learning well. So that it can be concluded that there is a significant effect of guided inquiry learning model on Substance and Material material towards the learning outcomes of VII grade students of Semester I of SMP Negeri 2 Siantar T.A.2017 / 2018.